Pengaruh Provitabilitas, Likuiditas, Solvabilitas, Rasio Aktivitas, Dan Investasi Terhadap Nilai Perusahaan - Putri Shela Nazib; Deannes Isynuwardhana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study was conducted to analyze the effect of profitability, liquidity, solvency, activity ratio, and investment on firm value. Firm value is one aspect to determine whether a company is good and has the right to be a place to invest. Firm value is the point of view of shareholders to the company related to the share price. The greater the company value, the more investors will be interested in investing in the company. Broadly speaking, price book value experienced fluctuations in increases and decreases in the 2018-2019 period. The population used is food and beverage companies listed on the IDX for the period 2018-2021 and produced a sample of 68 out of 17 companies. The method used is panel data regression technique with Eviews 12 software. The results in this study show that profitability, liquidity, isolvability, activity ratio have no effect on firm value, while investment has a negative effect on firm value.